Implementasi PSAK 109 Tentang Akuntansi Zakat dan Sedekah/Infak Studi Kasus pada Badan Amil Zakat Nasional di Tanah Datar, Sijunjung dan Sawahlunto - Rahmat Lailatul Qodri (Journal of Islamic and South East Asian Finance and Accounting, 2023)
The application of PSAK 109 concerning the accounting of zakat and alms / infaq in entities whose main operation is to collect and distribute zakat is very important. With the application of PSAK 109, it is hoped that the public's trust in the existing zakat management organization will increase, so that people prefer to distribute their zakat to zakat management organizations rather than issuing it personally directly to zakat recipients. The potential for zakat in Indonesia is very large, but it is not the same as the zakat collected by OPZ. This study aims to determine how the accounting treatment at BAZNAS Tanah Datar Regency, Sijunjung Regency, Sawahlunto City, and what the implications of the application of PSAK 109 on the performance of the collection and distribution of the three BAZNAS. This research belongs to the type of qualitative research, especially case studies. This research involved 3 cases, namely BAZNAS Tanah Datar, BAZNAS Sijunjung, and BAZNAS Sawahlunto. The results of this study show that the three BAZNAS still have not implemented PSAK 109 as a whole, and for BAZNAS Sijunjung, the application of PSAK 109 is still far from the accounting treatment according to PSAK 109